Research on the Digitization of Manufacturing Will Enhance the Competitiveness of the Value Chain Based on Advantage Comparison - You-Qun Wu; Huai-Xin Lu; Xin-Lin Liao; Jia-Ming Zhu (Complexity)
This paper uses WIOD data to calculate and analyze the dominant comparative advantage of Chinese manufacturing global value chain (GVC) based on the WWZ method and empirically studies the influence of digitization on the competitiveness of manufacturing GVC. The main findings are as follows: (1) The competitiveness of Chinese manufacturing GVC has been improved as a whole. The GVC competitiveness of different types of industries is quite different: GVC in middle- and low-knowledge-intensive industries have the highest competitiveness, while those with middle- and high-knowledge-intensive industries have the lowest competitiveness and apparent shortboard industries. (2) Digitization is conducive for enhancing the competitiveness of manufacturing GVC. In terms of industries, digitization has a significant positive effect on the GVC competitiveness of middle and high-knowledge-intensive industries but not on low knowledge ones. As for the sources of digital input, the positive effect is more outstanding. Also, it is more remarkable when it comes to the software and information technology service industry. (3) As for the mechanism of action, labor productivity is an effective way to improve the manufacturing GVC competitiveness digitally. Finally, after a robustness test, the positive effect of the digital input remains robust.